Integrated study on the deterioration investigation and intervention treatment of rural vacant traditional dwellings under population contraction - Tingshen Li; Xuehong Tan; Pin Liu (Journal of Asian Architecture and Building Engineering)
The rapid advancement of urbanization in China has exacerbated the contraction of many rural populations and as a result, the abandonment of many traditional dwellings. Therefore, the aim of this study was to properly analyze the deterioration of vacant traditional dwellings and propose ways to intervene and gradually solve the problem of vacant housing in rural areas. In this study, Wushao Village in Xuzhou City was selected for a pilot study of a typical village with a shrinking population. The research methods involved abundant field investigations to clarify the construction techniques and gather information on the deterioration of vacant traditional dwellings. Additionally, a comprehensive comparative analysis was performed to determine the appropriate treatments for deterioration problems. The results indicated that the vacant traditional dwellings in Wushao Village had various types of decay. Corresponding intervention measures and steps were proposed based on the specific causes of deterioration. This study demonstrated that comprehensive deterioration investigations and intervention treatments were able to effectively rehabilitate the integral status and preserve the authenticity of rural traditional dwellings. This will be conducive to the continuation and revitalization of the traditional features of villages.